Pediatric flexible bronchoscopy in the intensive care unit: A multicenter study - Atağ, Emine; Ünal, Füsun; Yazan, Hakan; Girit, Saniye; Uyan, Zeynep Seda; Ergenekon, Almala Pınar; Yayla, Esra; Merttürk, Edanur; Telhan, Leyla; Meral, Özge; Küçük, Hanife Büşra; Gündüz, Mehmet; et al. (Wiley, 2021)
Introduction Flexible bronchoscopy (FB) is frequently used for assessment and treatment of patients with respiratory diseases. Our aim was to investigate the contribution of FB to diagnosis and therapy in children admitted to the intensive care units (ICU) and to evaluate the safety of FB in this vulnerable population. Methods Children less than 18 years of age who underwent FB in the five neonatal and pediatric ICUs in Istanbul between July 1st, 2015 and July 1st, 2020 were included to the study. Demographic and clinical data including bronchoscopy indications, findings, complications, and the contribution of bronchoscopy to the management were retrospectively reviewed. Results One hundred and ninety-six patients were included to the study. The median age was 5 months (range 0.3-205 months). The most common indication of FB was extubation failure (38.3%), followed by suspected airway disease. Bronchoscopic assessments revealed at least one abnormality in 90.8% patients. The most common findings were airway malacia and the presence of excessive airway secretions (47.4% and 35.7%, respectively). Positive contribution of FB was identified in 87.2% of the patients. FB had greater than 1 positive contribution in 138 patients and 80.6% of the patients received a new diagnosis. Medical therapy was modified after the procedure in 39.8% and surgical interventions were pursued in 40% of the patients. Therapeutic lavage was achieved in 18.9%. There were no major complications. Conclusion Flexible bronchoscopy is a valuable diagnostic and therapeutic tool in neonatal and pediatric ICUs and is not associated with major complications.
Keywords: Bronchoscopy; Critical Care; Pulmonology